Adsorption Kinetic and Isotherm of Solution Pair of Methylene Blue and Crystal Violet by Algae-Silica-Magnetite Hybrid Adsorbent on Porphyridium sp. Algae. Issue 1 (January 2021) - Permatasari, D; Buhani,; Rilyanti, M; Suharso,
Abstract: Algae-silica-magnetite hybrid (PSM) from Porphyridium sp. algae has been successfully synthesized using precursor tetraethyl orthosilicate (TEOS) and coating with magnetite particles (Fe3 O4 ) via a sol-gel process. The resulting adsorbent was applied for adsorption of solution pair of methylene blue (MB) and crystal violet (CV). The result of the analysis using the Infrared Spectrometer (IR) showed that in the PSM adsorbent there is an organic groups derived from Porphyridium sp. algae while silanol and siloxane group derived from silica matrix. In addition, surface morphology analysis results using Scanning Electron Microscopy With Energy Dispersive X-Ray (SEM-EDX) showed PSM surface has more heterogeneous than algae-silica hybrid (PS). The adsorption of solution pair of MB and CV by PSM was done under the experimental conditions of adsorbent of 0.1 g, interaction pH of 8, contact time of 90 min, and adsorbate concentration of 0.5 mmol L −1 . The adsorption kinetics data indicate that it tends to follow the pseudo second order model with a correlation coefficient (R 2 ) of 0.989 and 0.965 respectively. While, the adsorption isotherm model tends to follow Freundlich model.